2013
DOI: 10.1074/jbc.m113.472837
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Sequence Tunes Ligand Sensitivity in Phospholipid-regulated Hormone Receptors

Abstract: Background: NR5A nuclear receptors are important pharmaceutical targets with poorly understood ligand regulation. Sequence divergence has potentially altered their ligand response in model organisms. Results: Sequence divergence has differentially impacted ligand binding and protein dynamics in NR5A orthologs. Conclusion: Mouse LRH-1 is a phospholipid-responsive receptor, whereas Drosophila NR5A2 is not. Significance: Mice are viable therapeutic models for LRH-1-dependent diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 47 publications
1
25
1
Order By: Relevance
“…Expression of hLRH-1 normalizes hepatic lipids and improves glucose homeostasis. Distinct structural features at the mouth of the ligand-binding pocket allow human LRH-1 (hLRH-1) to efficiently bind phospholipid ligands compared with mouse LRH-1 (mLRH-1) (23,43). To test whether hLRH-1 rescues hepatic phenotypes observed in Lrh-1 AAV8-Cre mice, we humanized mouse livers by simultaneously infecting mice with AAV8-Cre-and AAV8-FLAG-tagged hLRH-1 (Lrh-1 AAV8-Cre+hLrh1 ), which eliminates mLRH-1, while introducing epitope-tagged hLRH-1 in approximately 80% of hepatocytes (44), as shown in Figure 6A.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of hLRH-1 normalizes hepatic lipids and improves glucose homeostasis. Distinct structural features at the mouth of the ligand-binding pocket allow human LRH-1 (hLRH-1) to efficiently bind phospholipid ligands compared with mouse LRH-1 (mLRH-1) (23,43). To test whether hLRH-1 rescues hepatic phenotypes observed in Lrh-1 AAV8-Cre mice, we humanized mouse livers by simultaneously infecting mice with AAV8-Cre-and AAV8-FLAG-tagged hLRH-1 (Lrh-1 AAV8-Cre+hLrh1 ), which eliminates mLRH-1, while introducing epitope-tagged hLRH-1 in approximately 80% of hepatocytes (44), as shown in Figure 6A.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, residues from the N-terminal part of helix H7 (T423, L424) and the preceding loop L6-7 (Q419, A420, G421, A422) contact the solvent exposed part of the bound ligand. Direct interactions between bound PIP 3 and hLRH-1 loop L6-7 are notable, as amino acid sequence variations in L6-7 of human, mouse and Drosophila receptor orthologs (hLRH-1, mLRH-1 and dmFTZ-f1) were shown to differentially tune the sensitivity of NR5A receptors to phospholipid ligand binding (Krylova et al, 2005; Musille et al, 2013; Sablin et al, 2003). In total, 10 hydrogen bonds, excluding those mediated by water molecules, coordinate and organize the ligand-protein interface outside the receptor hormone pocket (see Table S2 for details); these electrostatic contacts are formed in addition to the extensive van der Waals interactions that dominate ligand-receptor association inside the hydrophobic pocket.…”
Section: Resultsmentioning
confidence: 99%
“…In both PIP 3 bound receptors, the exposed ligand head group is in direct contact with the NR5A residues from loop L6-7. In different NR5A orthologs, primary sequence variations in this loop control the sensitivity of NR5A receptors to phospholipid binding and ligand-mediated regulation (Krylova et al, 2005; Musille et al, 2013; Sablin et al, 2003). These observations reinforce our earlier hypothesis that signaling phosphatidylinositols play a regulatory role in NR5A function (Blind et al, 2012; Blind et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have demonstrated a role for PS in the regulation of LRH-1's target genes, recent HDX studies that compared LRH-1 bound to E. coli PLs and DLPC demonstrated increased flexibility in both the mouth of the ligand binding pocket and the AF-2 region in DLPC-bound LRH-1 (20). Furthermore, stabilizing the mouth of the LBP in apo-hLRH-1 by replacing residues 419 -424 with the corresponding mouse LRH-1 sequence enhances binding of the co-activators TIF-2 and PGC1␣ (52). In the absence of PLs, the receptor accesses a greater amount of conformational space and readily interacts with co-repressors.…”
Section: Discussionmentioning
confidence: 99%